The role of alloyed strontium in the microstructures and alkaline electrochemistry of Mg-5Al-4Sn alloys - Van Sy, L. (Royal Society of Chemistry, 2020)
In this study, strontium is used as an alloying element for improving the pitting resistance of Mg-5Al-4Sn based alloys in an alkaline solution. Potentiodynamic polarization measurements suggest that the addition of strontium increases the robustness of the pitting resistance as a result of the higher pitting potential and wider range of passive potential. Electrochemical impedance spectroscopy (EIS) confirms the formation of a solid passive film on the alloy surface due to a significant increase in the passive film and the charge transfer resistance, as well as lower film and double layer constant phase element magnitude values. Additionally, the potentiostatic polarisation results also show a lower passive current density and passive film stability, resulting in an increase in the breakdown time when the amount of strontium added to the alloy increases from 0.0 to 1.0 wt. Furthermore, the scanning electron microscopy results indicate that insignificant corrosion is observed on alloy specimens containing strontium, whereas there is fierce corrosion on alloy based surfaces. This robust corrosion resistance could be attributed to the Î±-grain reduction and refined precipitates at the alloy grain boundaries, resulting in promoted formation of the passive film which is formed from a mixture of magnesium, aluminum and tin oxides/hydroxides, as confirmed by the X-ray photoelectron spectroscopy results. Â© The Royal Society of Chemistry 2020.